Enhancing the productivity of high-magnesium soil and water resources in Central Asia through the application of phosphogypsum - Vyshpolsky, F.F.; Qadir, Manzoor; Karimov, Akmal A.; Mukhamedjanov, K.; Bekbaev, U.; Paroda, R.; Aw-Hassan, Aden A.; Karajeh, F. (2008)
Recent evidences from some irrigated areas worldwide, such as Central Asia, suggest that water used for irrigation contains magnesium (Mg2?) at levels higher than calcium (Ca2?). Excess levels of Mg2? in irrigation water and/or in soil, in combination with sodium (Na2?) or alone, result in soil degradation because of Mg2? effects on the soil's physical properties. More than 30 per cent of irrigated lands in Southern Kazakhstan having excess levels of Mg2? are characterized by low infiltration rates and hydraulic conductivities. The consequence has been a gradual decline in the yield of cotton (Gossypium hirsutum L.), which is commonly grown in the region. These soils require adequate quantities of Ca2? to mitigate the effects of excess Mg2?. As a source of Ca2?, phosphogypsum?a byproduct of the phosphorous fertilizer industry?is available in some parts of Central Asia. In participation with the local farming community, we carried out a 4-year field experiment in Southern Kazakhstan to evaluate the effects of soil application of phosphogypsum?0, 4_5, and 8_0 metric ton per hectare (t ha_1)?on chemical changes in a soil containing excess levels of Mg2?, and on cotton yield and economics. The canal water had Mg2? to Ca2? ratio ranging from 1_30 to 1_66 during irrigation period. The application of phosphogypsum increased Ca2? concentration in the soil and triggered the replacement of excess Mg2? from the cation exchange complex. After harvesting the first crop, there was 18 per cent decrease in exchangeable magnesium percentage (EMP) of the surface 0_2m soil over the pre- experiment EMP level in the plots where phosphogypsum was applied at 4_5 t ha_1, and a 31 per cent decrease in EMP in plots treated with phosphogypsum at 8 t ha_1. Additional beneficial effect of the amendment was an increase in the soil phosphorus content. The 4-year average cotton yields were 2_6 t ha_1 with 8 t ha_1 phosphogypsum, 2_4 t ha_1 with 4_5 t ha_1 phosphogypsum, and 1_4 t ha_1 with the control. Since the amendment was applied once at the beginning, exchangeable Mg2? levels tended to increase 4 years after its application, particularly in the treatment with 4_5 tha_1 phosphogypsum. Thus, there would be a need for phosphogypsum application to such soils after every 4-5 years to optimize the ionic balance and sustain higher levels of cotton production. The economic benefits from the phosphogypsum treatments were almost twice those from the control.